Inhibition of human immunodeficiency virus type 1 replication in human T cells by retroviral-mediated gene transfer of a dominant-negative Rev trans-activator. - Bevec, D (1992)
Human immunodeficiency virus type 1 (HIV-1) is the causative agent of the acquired immunodeficiency syndrome (AIDS). Currently, no satisfactory treatment for this viral disease is available. Somatic gene therapy has been proposed as an alternative to conventional therapies. Several antiviral gene therapy approaches including ribozymes, antisense inhibition, and RNA-decoy strategies, as well as dominant-negative mutants of HIV-1 proteins (Gag, Tat, and Rev) have been suggested. To prove the concept of trans-dominant inhibition of HIV-1 replication, we transduced CEM cells with a retroviral vector encoding a dominant-negative rev gene. Amplification of integrase-specific proviral sequences from high molecular weight DNA indicated successful HIV-1 human T-lymphotropic virus type IIIB (HTLV-IIIB) infection of all cells. In contrast to CEM cells and CEM cells expressing the rev wild-type (wt) gene, infection of two CEM-RevM10 clones with HIV-1 did not result in the release of significant levels of p24 Gag antigen as measured by antigen capture assay, indicating a block in HIV-1 replication due to the presence of the trans-dominant Rev protein. Furthermore, the parental CEM cells as well as CEM cells expressing the Rev wt protein were effectively killed in the course of the HIV-1 infection, whereas all CEM cells expressing the RevM10 protein were unaffected in their growth rate.